Environment-friendly short-term protection of palm wood against mould and rot fungi. Issue 4 (7th August 2016) - Bahmani, Mohsen; Schmidt, Olaf; Fathi, Leila; Frühwald, Arno
Abstract: Felled palm trunks are susceptible to fungi as long as their moisture content is above fibre saturation. During this period, palm wood has to be protected against mould and rot fungi. The study was aimed at testing environment-friendly organic acids for their protecting efficiency. Small samples of date palm ( Phoenix dactylifera ) and oil palm ( Elaeis guineensis ) wood were treated with weak organic acids and subsequently infected by moulds and wood-decay fungi. Short dipping of the samples in solutions of 5% acetic acid and propionic acid, respectively, protected all samples for two months from colonization by Aspergillus niger, Penicillium sp., Cladosporium sp. and by a natural infection. Boric acid (4%) used in practice for protection was ineffective. Decay tests with the white-rot fungus Pleurotus ostreatus, the brown-rot species Coniophora puteana and the soft-rot fungus Chaetomium globosum showed that both acids prevented most samples from fungal colonization for three weeks and reduced the decay considerably during two months.